Study of the Consciousness Energy Healing Treatment and It’s Effect on the Isotopic Abundance Ratio of Ascorbic Acid (Vitamin C) - Mahendra Kumar Trivedi; Alice Branton; Dahryn Trivedi; Snehasis Jana (Journal of Advances in Nanotechnology, 2021)
Ascorbic acid is a water-soluble vitamin (Vitamin C) essential for both the plants and animals for the metabolic process. In this study, the liquid chromatography-mass spectrometry (LC-MS) analytical technique was used to characterize the structural properties and isotopic abundance ratio to evaluate the effect of the Trivedi Effect®-Consciousness Energy Healing Treatment on L-ascorbic acid compared to the control sample. The ascorbic acid sample was divided into control and treated parts. Only the treated part received the Trivedi Effect®-Consciousness Energy Healing Treatment remotely by a well-known Biofield Energy Healer, Mahendra Kumar Trivedi. The control and treated samples showed a chromatographic peak at retention time (Rt) 1.8 minutes exhibited the deprotonated molecular ion peak at m/z 175 (M-H)- (calculated for C6H7O6-, 175.02) in the mass spectra. The peak area of the treated sample (12817614.01) was significantly increased by 8.81% compared to the control sample (11779918.9). The LC-MS based isotopic abundance ratio of PM+1/PM (2H/1H or 13C/12C or 17O/16O) in the treated ascorbic acid was significantly increased by 23.22% compared with the control sample. Thus,13C, 2H, and17O contributions from (C6H7O6)- to m/z 176 in the treated ascorbic acid were significantly increased compared with the control sample. The increased isotopic composition of the treated ascorbic acid might have altered the neutron to proton ratio in the nucleus. The changes in isotopic abundance could be due to changes in nuclei possibly through the interference of neutrino particles via the Trivedi Effect®-Consciousness Energy Healing Treatment. The increased isotopic abundance ratio and peak area of the treated ascorbic acid may increase the intra-atomic bond strength and its stability. This novel ascorbic acid after the Trivedi Effect®-Consciousness Energy Healing Treatment would be very useful to design more efficacious pharmaceutical formulations against scurvy, obesity, cardiovascular diseases, hypertension, rheumatoid arthritis, Alzheimer's disease, cancer, etc.
Keywords: Consciousness Energy Healing Treatment